2020
DOI: 10.1152/ajpheart.00177.2020
|View full text |Cite
|
Sign up to set email alerts
|

Sensory nerve-mediated and nitric oxide-dependent cutaneous vasodilation in normotensive and prehypertensive non-Hispanic blacks and whites

Abstract: Overt hypertension is known to reduce cutaneous sensory nerve-mediated and nitric oxide (NO)-dependent vasodilation, but the effect of subclinical increases in blood pressure (i.e., prehypertension) is unknown. The combined effect of race and prehypertension is also unknown. In this study, we found that prehypertension reduces cutaneous sensory nerve-mediated and NO-dependent vasodilation in both non-Hispanic white and black populations, with the greatest reductions observed in prehypertensive non-Hispanic bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 56 publications
(39 reference statements)
4
20
0
Order By: Relevance
“…Black or African American adults (Hurr et al, 2018;Miller et al, 2021;Patik et al, 2018;Wong et al, 2020). This might indicate endothelial dysfunction and acutely increased cardiovascular risk in women currently using OCP.…”
Section: Endothelium-dependent Vasodilatationmentioning
confidence: 99%
“…Black or African American adults (Hurr et al, 2018;Miller et al, 2021;Patik et al, 2018;Wong et al, 2020). This might indicate endothelial dysfunction and acutely increased cardiovascular risk in women currently using OCP.…”
Section: Endothelium-dependent Vasodilatationmentioning
confidence: 99%
“…Furthermore, our previous work demonstrated that the administration of 98% cinnamaldehyde via intradermal microdialysis increased cutaneous vascular conductance by ;37 %max from baseline. 16 Noteworthy, the elevation in cutaneous vascular conductance associated with the administration of cinnamaldehyde by intradermal microdialysis was comparable to the elevations observed by both local skin heating to 398C 3,29,30 and whole-body heating, [30][31][32][33] with each heating modality increasing cutaneous vascular conductance to approximately 30-50 %max from baseline. Taken together, these findings show that TRPA1 channel activation in humans in vivo can induce a robust cutaneous vasodilatory response.…”
Section: Discussion Trpa1 Channel-induced Cutaneous Vasodilationmentioning
confidence: 59%
“…The pathophysiology of sensory neuropathy is linked to microvascular and endothelial dysfunction (Cameron et al., 2001) and we originally hypothesized that this dilatation would be attenuated in our patient group. Indeed, prehypertensive adults and non‐hypertensive black men and women have an attenuated cutaneous sensory nerve‐mediated vasodilatation response, reflective of and accompanied by reductions in endothelium‐dependent NO‐mediated dilatation (Patik et al., 2018; Turner et al., 2020; Wong et al., 2020). In these studies, as with ours, local heating applied to the skin was used to activate the sensory nerve‐mediated increase in skin blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we did not directly inhibit sensory nerves and as such, the direct contribution of sensory nerves to our responses cannot be quantified. Local inhibition of sensory nerves with topical anaesthetic cream attenuates the initial peak by ∼50% in the forearm (Hodges et al., 2015; Minson et al., 2001; Wong et al., 2020). Our data did not reveal a difference in the magnitude of the initial peak response in women with a history of PE, and we hypothesize that this is indicative of a preserved neurogenically mediated dilatation in these women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation